[OP.8D.03] MEASUREMENT OF ARTERIAL STIFFNESS BY ULTRAFAST ECHO: COMPARISON WITH ECHOTRACKING IN NORMOTENSIVE SUBJECTS AND HYPERTENSIVE PATIENTS. (September 2016) - Marais, L.; Pernot, M.; Khettab, H.; Tanter, M.; Messas, E.; Zidi, M.; Laurent, S.; Boutouyrie, P.
Abstract : Objective: The question whether arterial stiffness in hypertension is increased solely because of increased arterial pressure is not solved. Because measurement of arterial stiffness is highly dependent on measurement of blood pressure (BP), the development of methods independent of BP is necessary for clarifying this question. Ultrafast echography (UFE, Supersonic Imagine, Aix en Provence, France) makes use of very fast sampling rate (up to 10 kHz), so transient events such as pressure wave arrival can be tracked. From the spontaneous pressure wave transit time, the stiffness of the wall material can be measured with no need of BP. This method has never been tested against classical echotracking (Artlab, Esaote, Maastricht, NL) and carotid to femoral pulse wave velocity (cf-PWV, Sphygmocor, AtCor, Sydney, Australia). Design and method: We included 56 subjects, 27 normotensives (NT) and 29 essential hypertensives (HT), matched for age and sex. We compared UFE to echotracking and cf-PWV. Measurements were performed in resting conditions. We optimized UFE algorithms for pressure wave detection and tracking, for both foot of the wave (FW) and dicrotic notch (DN) PWV. Results: Feasibility appears good (FW: 78%, DN: 96%). The relations of arterial stiffness with age and blood pressure were stronger for echotracking and cf-PWV than for UFE. DN wave fronts appeared better associated with cf-PWV (r = 0.32, p < 0.001) and carotid PWV (r = 0.47, p < 0.001). FW was not associated with cf-PWV nor with carotid PWV. The residuals between DN and carotid PWV were not associated with BP or age. Similar associations between DN and cf-PWV/carotid PWV were found in NT and HT. Conclusions: After optimizing algorithms for wave front identification and tracking, UFE appears as a promising technique for assessing arterial stiffness. DN showed the best associations with echotracking, whereas FW did not provide meaningful data. As previously shown by Hermeling et al (J Hypertens 2008 and 2009), FW is not appropriate for local stiffness measurement likely because of very early wave reflections.